2018
DOI: 10.1021/acs.biomac.8b00585
|View full text |Cite
|
Sign up to set email alerts
|

Preserving Cellulose Structure: Delignified Wood Fibers for Paper Structures of High Strength and Transparency

Abstract: To expand the use of renewable materials, paper products with superior mechanical and optical properties are needed. Although beating, bleaching, and additives are known to improve industrially produced Kraft pulp papers, properties are limited by the quality of the fibers. While the use of nanocellulose has been shown to significantly increase paper properties, the current cost associated with their production has limited their industrial relevance. Here, using a simple mild peracetic acid (PAA) delignificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 56 publications
2
75
1
Order By: Relevance
“…19 The ζ-potential of the control holocellulose fibres (−25.4 ± 1.5 mV) corresponded well to previous results obtained with the same type of fibres. 27 Conductometric titration on the fibres also revealed that the LPMOs increased the carboxyl content by 27% and 88% compared to the control. The obtained carboxyl contents were 0.38 and 0.53 mmol g −1 for NcLPMO9E and NcLPMO9F, respectively (Fig.…”
Section: Lpmo-assisted Holocellulose Fibrillationmentioning
confidence: 88%
See 2 more Smart Citations
“…19 The ζ-potential of the control holocellulose fibres (−25.4 ± 1.5 mV) corresponded well to previous results obtained with the same type of fibres. 27 Conductometric titration on the fibres also revealed that the LPMOs increased the carboxyl content by 27% and 88% compared to the control. The obtained carboxyl contents were 0.38 and 0.53 mmol g −1 for NcLPMO9E and NcLPMO9F, respectively (Fig.…”
Section: Lpmo-assisted Holocellulose Fibrillationmentioning
confidence: 88%
“…The holocellulose fibres were prepared according to a previously reported method. 27 Briefly, softwood spruce sticks were first soaked in water under vacuum, and subsequently treated with 4% (w/w) peracetic acid (PAA) for 45 min at 85°C. The PAA solution was prepared by diluting 38-40% (w/w) PAA solution (Sigma-Aldrich), followed by adjusting the pH to 4.6 using NaOH before the reaction.…”
Section: Preparation Of Holocellulosementioning
confidence: 99%
See 1 more Smart Citation
“…The Klason lignin content was measured according to the standard TAPPI T222 om-02, and sugar analysis was carried out after acid hydrolysis, using a highperformance anion-exchange chromatography Dionex ICS-3000 (Thermo Fisher Scientific Inc., USA) with references of rhamnose, arabinose, galactose, glucose, xylose, and mannose (Herrera et al 2018). The hemicellulose and cellulose contents were calculated based on glucomannan and xylan as the principal hemicelluloses in spruce (Yang et al 2018). Xylan content was calculated based on xylose and arabinose, glucomannan content was calculated based on galactose, glucose, and mannose contents using a 1:3 ratio of glucose: mannose (Sjöström 1993;Walker 2006;Yang et al 2018), and cellulose content was then calculated based on the remaining glucose content.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…The hemicellulose and cellulose contents were calculated based on glucomannan and xylan as the principal hemicelluloses in spruce (Yang et al 2018). Xylan content was calculated based on xylose and arabinose, glucomannan content was calculated based on galactose, glucose, and mannose contents using a 1:3 ratio of glucose: mannose (Sjöström 1993;Walker 2006;Yang et al 2018), and cellulose content was then calculated based on the remaining glucose content.…”
Section: Chemical Compositionmentioning
confidence: 99%